THE ROLE OF HIGHER EDUCATION INSTITUTIONS IN ACHIEVING SDGs IN INDONESIA - Ismet Sulila (International Interdisciplinary Conference on Sustainable Development Goals, 2022)
The involvement of Higher Education Institutions in overcoming problems in society has been mandated by the third pillar of TridharmaPerguruan Tinggi (Three Pillars of Higher Education),namely community service. Empowerment and development of rural communities, as also mandated by Law number 6 of 2014 concerning Villages, is one of the services of higher education institutions to the community and village government. The real form of higher education institution policy programs is carrying out a Sustainable Village Development program based on the Sustainable Development Goals (SDGs). The form of activity is carried out through community service activities by focusing on identifying and developing regional potentials to deal with various development problems in rural areas. This current article describes the results of field study on the important role of higher education institutions in achieving the SDGs through village development in Tomini Bay area, particularly in Gorontalo Province. The focus of this study includes: 1) the contribution of higher education institutions in village development through the SDGs, 2) the prioritization of use of village funds, and 3) Good Governance and Innovation.